A Study on Cultural Conflicts Faced by Chinese Enterprises in Africa—A Case of Huajian Group - WU, Yiming; ZHAO, Guoxiang (Advances in Social Sciences Research Journal, 2018)
With the development of the "Belt and Road" initiative, an increasing number of Chinese enterprises have begun to adopt “Going Global Strategy”. The positive trend, however, is now impeded by various cross-cultural conflicts which will be more complicated and severe as the communication continues, which implies an effective cross-cultural management is essential for every Chinese enterprise during the process of going international. From the cross-cultural perspective ,this paper aims to study the challenges and problems faced by Huajian Group , the world's largest high-end leather female shoes manufacturer–Huajian Group , followed by some effective measurements.